2016
DOI: 10.1186/s40580-016-0083-9
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional nanomaterials for the control of stem cell fate

Abstract: Current stem cell therapy suffers low efficiency in giving rise to differentiated cell lineages, which can replace the original damaged cells. Nanomaterials, on the other hand, provide unique physical size, surface chemistry, conductivity, and topographical microenvironment to regulate stem cell differentiation through multidimensional approaches to facilitate gene delivery, cell–cell, and cell–ECM interactions. In this review, nanomaterials are demonstrated to work both alone and synergistically to guide sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 73 publications
0
27
0
Order By: Relevance
“…120 Other studies have shown increased osteogenesis of MSCs on the surface of polycaprolactone nanofibers and increased NSC proliferation on the surface of a graphene oxide-coated polycaprolactone nanofibers in vitro. 119 These results suggest that ECM modification may be capable of promoting stemness. Thus, delivery of these synthetic material in vivo may recapitulate similar effects to promote proper tissue restoration and phenotype recovery.…”
Section: Secretome-based Rejuvenationmentioning
confidence: 89%
See 2 more Smart Citations
“…120 Other studies have shown increased osteogenesis of MSCs on the surface of polycaprolactone nanofibers and increased NSC proliferation on the surface of a graphene oxide-coated polycaprolactone nanofibers in vitro. 119 These results suggest that ECM modification may be capable of promoting stemness. Thus, delivery of these synthetic material in vivo may recapitulate similar effects to promote proper tissue restoration and phenotype recovery.…”
Section: Secretome-based Rejuvenationmentioning
confidence: 89%
“…118 Other strategies utilized graphene and graphene oxide-based scaffolds to improve osteogenic and chondrogenic potential of MSCs in vitro. 119 Similarly, graphene nanoparticles have been used to increase long-term proliferation of human NSCs in vitro. 120 Other studies have shown increased osteogenesis of MSCs on the surface of polycaprolactone nanofibers and increased NSC proliferation on the surface of a graphene oxide-coated polycaprolactone nanofibers in vitro.…”
Section: Secretome-based Rejuvenationmentioning
confidence: 99%
See 1 more Smart Citation
“…An interesting strategy for use of MSCs is based on the production of nanoscaffolds that mimic the physical characteristics of human skin. 131,132 The incorporation of SCs into this nanoscaffold resulted in an engineered wound dressing holding a “cocktail” of stem cells, growth factors, and the matrix itself. 129,133 Polymeric nanofibers also had a recent surge in the tissue regeneration field.…”
Section: Stem Cell Incorporated Nanoscaffoldsmentioning
confidence: 99%
“…Radionuclides either can be directly labeled ( 11 C, 18 F, 76 Br and 124 I) or can be chelated ( 64 Cu, 68 Ga, 89 Zr, 90 Y, 99m Tc, and 177 Lu) onto a wide variety of NP. 131 imaged.…”
Section: Single-photon Emission Computed Tomography Cell Imaging Wimentioning
confidence: 99%